Top leadership, U.S.A. - Hunter, Floyd (Chapel Hill, 1959)
WHO MAKES national policies? Who them out? Are community carries leaders also national leaders? Do these men as a single group conspire against the rest of the nation? How do state leaders, corporation executives, profes- sional men in associations, and even international leaders function as policy makers? These questions are among those answered in Top Leadership, U.S.A., by Floyd Hunter, the author of Community Power Structure, which es- tablished a new method for studying the relationships of men in power. That method was applied in a nationwide field study made by Mr. Hunter, in which he visited during the past five years all cities in the United States of more than one million population and scores of smaller cities in a majority of the states. He interviewed association leaders, community leaders, North and South Carolina leaders, American and Japanese textile leaders, housing leaders, elected and appointed leaders, and, above all, he talked with the majority of men in the United States who are designated by their peers as top leaders in making and establishing opinions, policies, and decisions. He questioned them about their relations to each other, the influence of associations, the expansion of community and state policies, specific issues such as housing and textile problems, the achievement or the blocking of policy goals, the relative power of government, the concept of sixty ruling fam- ilies, and the motivation of the nation's most powerful men. The result is Top Leadership, U.S.A., which shows empirically that there is a distinct and identifiable group of men leading the American people. Mr. Hunter lists the names of these men. He demonstrates that policies are decided and implemented, not by magic but by men, not altogether by men elected to public office, but through coordinate actions of many formal and informal groups of interested men. The leaders operate within power structures that overlap and coalesce. The most important of these power structures in national policy development are the community and the corporation pyramids of power. From such interest groups, individuals are selected by others like them to man authoritative national policy committees and com- missions or individual offices of trust. These men, the principal actors in the drama of power on our American stage, lead this country.
Keywords: Leadership